2006
DOI: 10.1007/s10750-005-6427-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Lake Prespa Jeopardizing the Ecosystem of Ancient Lake Ohrid?

Abstract: Lake Prespa and Lake Ohrid, located in south-eastern Europe, are two lakes of extraordinary ecological value. Although the upstream Lake Prespa has no surface outflow, its waters reach the 160 m lower Lake Ohrid through underground hydraulic connections. Substantial conservation efforts concentrate on oligotrophic downstream Lake Ohrid, which is famous for its large number of endemic and relict species. In this paper, we present a system analytical approach to assess the role of the mesotrophic upstream Lake P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(193 citation statements)
references
References 26 publications
6
185
1
1
Order By: Relevance
“…Its hydrological balance is regulated via 37.3 m 3 s -1 inflow of which * 25% origins from direct precipitation, * 25% from river input and * 50% from the karst aquifers. Outflow is regulated through the river Crni Drim (* 60%) and evaporation (* 40%; Matzinger et al, 2006). The average surrounding air temperature is 26°C during summer, and -1°C during winter, while the average annual precipitation is * 750 mm year -1 .…”
Section: Sampling Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Its hydrological balance is regulated via 37.3 m 3 s -1 inflow of which * 25% origins from direct precipitation, * 25% from river input and * 50% from the karst aquifers. Outflow is regulated through the river Crni Drim (* 60%) and evaporation (* 40%; Matzinger et al, 2006). The average surrounding air temperature is 26°C during summer, and -1°C during winter, while the average annual precipitation is * 750 mm year -1 .…”
Section: Sampling Sitementioning
confidence: 99%
“…1 Location of Lake Ohrid at the Balkan Peninsula (right corner). Topographic and bathymetric map of Lake Ohrid showing the sampling locations at each transect: Kalishta, Struga, Sateska, Ohrid, Peshtani and St. Naum as result of the global warming and local anthropogenic impact (Matzinger et al, 2006(Matzinger et al, , 2007.…”
Section: Sampling Sitementioning
confidence: 99%
“…A deeper body is thought to be better for maneuvering in structured habitats, whereas a streamlined body is thought to be adapted for minimizing drag while searching for food in open water (Webb, 1984). Study on perch (Svanbäck & Eklöv, 2002;2006) indicated that perch caught in the littoral habitat, independent of size, had a deeper body, larger head, and mouth and longer fins than perch caught in the pelagic zone. Bearing in mind that the Lake Skadar is generally shallow and subject to large surface area fluctuations obtained results are in correlation with general littoral distribution of R. prespensis (Milošević et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These two lakes are located between two mountains Galičica and Baba. Lake Prespa has no surface outflow and it is connected with Lake Ohrid by underground hydraulic connections and karst channels (Anovski et al, l991;Eftimi & Zoto, 1996;Eftimi et al, 2002;Matzinger et al, 2006).…”
Section: Study Areamentioning
confidence: 99%
“…Alternatively, a reduced inflow could have caused the lowstand of Lake Prespa around 74 ka. Today, the annual inflow is 534 × 10 6 m 3 or about 15 % of the entire volume of the lake (Matzinger et al, 2006a). River runoff from numerous small streams (56 %) and direct precipitation (35 %) form the main proportion of the annual inflow.…”
Section: Interpretation and Conclusionmentioning
confidence: 99%